Preventive herd management practices and their effect on lamb mortality in Ethiopia - Genfors, E.; Magnusson, Ulf; Moliso, M.M.; Wieland, Barbara; König, Ulrika; Hallenberg, Gunilla S.; Båge, R. (Springer, 2023)
According to previous studies, lamb mortality is high in the Ethiopian highlands. The present study aims to evaluate the execution of preventive sheep herd health management practices with respect to if, and how, such practices are linked to occurrence of lamb mortality. Interviews were performed with 74 sheep-owning households participating in a capacity development program on livestock and 69 households not participating in such program. To evaluate the impact of combinations of performed practices, a scoring system was developed—the households retrieved a higher score the more desired routines were accomplished. To identify which practices had the highest impact on lamb mortality, a similar score was calculated for each phase of the sheep reproductive year, creating sub-scores for each phase. The results showed a significant (p < 0.05) negative correlation between the total number of performed practices and occurrence of lamb mortality, indicating a lower occurrence of lamb mortality the more desired practices implemented. Further analysis of sub-scores showed significant (p < 0.05) negative correlations between a higher number of performed desired practices during gestation period and during lambing. Conclusively, the study indicates that preventive herd management routines are beneficial for lamb survival, foremost when enforced during the gestation period and around lambing—hence, this is where to focus future interventions.